An environmental friendly anti-ageing additive to bitumen. (1st May 2016) - Gawel, Irena; Czechowski, Franciszek; Kosno, Jacek
Highlights: Addition of imidazoline to bitumen before ageing reduces oxygen uptake by bitumen. Imidazoline decreases asphaltene formation upon aging and its molecular weight. Imidazoline improves colloidal stability of bitumen. Imidazoline added to bitumen acts as a dispersant and an anti-oxidant. Imidazoline can be used as an environmental friendly ageing inhibitor to bitumen. Abstract: Oleic imidazoline obtained from natural resource was tested as an ageing inhibitor to bitumen. The effect of oleic imidazoline on the reduction in bitumen oxidative ageing was studied using various analytical methods. Three bitumens of different origin (O, L andN ) and their mixes with 1 wt.%. of oleic imidazoline were subjected to ageing by RTFOT method. The aged bitumens with and without imidazoline were analyzed. Colloidal stability of aged bitumens was enhanced by addition of imidazoline confirming the ability of imidazoline to act as a dispersant. GPC analysis of asphaltenes separated from bitumens has confirmed a dispersing ability of imidazoline. The kinetic of oxygen uptake by the bitumens, taken as a determinant of their susceptibility to ageing, showed a decrease in oxygen uptake as a result of imidazoline addition. Amount of oxygen uptake corresponds to ageing index expressed by the viscosity ratios after and before ageing. This indicates that imidazoline can also act as an anti-oxidant to bitumen. Depending on the chemical nature of the bitumen, the dispersant or antioxidant effect of imidazoline prevail. The study has shown that imidazoline can be used as an environmental friendly ageing inhibitor to bitumen.